Death in paradise. Season fourteen [videorecording (DVD)] - Thorogood, Robert (BBC, 2025)
There's a stranger in paradise a new detective with a dazzling assortment of outlandish puzzles to solve. Don Gilet joins the sun-soaked crime drama as DI Wilson, a detective with a very personal reason for being on Saint Marie but a serious lack of interpersonal skills. His sleuthing is quickly put to the test though in the case of the three Santa Clauses found dead under almost impossible circumstances, a murder on a zipline and a 'rum' case of poisoning. But Wilson also has a mystery of his own to solve - one that's very close to home.